Opportunities and Challenges of Low-Carbon Hydrogen via Metallic Membranes. (September 2020) - Liguori, Simona; Kian, Kourosh; Buggy, Nora; Anzelmo, Bryce H.; Wilcox, Jennifer
Abstract: Today, electricity & heat generation, transportation, and industrial sectors together produce more than 80% of energy-related CO2 emissions. Hydrogen may be used as an energy carrier and an alternative fuel in the industrial, residential, and transportation sectors for either heating, energy production from fuel cells, or direct fueling of vehicles. In particular, the use of hydrogen fuel cell vehicles (HFCVs) has the potential to virtually eliminate CO2 emissions from tailpipes and considerably reduce overall emissions from the transportation sector. Although steam methane reforming (SMR) is the dominant industrial process for hydrogen production, environmental concerns associated with CO2 emissions along with the process intensification and energy optimization are areas that still require improvement. Metallic membrane reactors (MRs) have the potential to address both challenges. MRs operate at significantly lower pressures and temperatures compared with the conventional reactors. Hence, the capital and operating expenses could be considerably lower compared with the conventional reactors. Moreover, metallic membranes, specifically Pd and its alloys, inherently allow for only hydrogen permeation, making it possible to produce a stream of up to 99.999+% purity. For smaller and emerging hydrogen markets such as the semiconductor and fuel cell industries, Pd-based membranes may be an appropriate technology based on the scales and purity requirements. In particular, at lower hydrogen production rates in small-scale plants, MRs with CCUS could be competitive compared to centralized H2 production. On-site hydrogen production would also provide a self-sufficient supply and further circumvent delivery delays as well as issues with storage safety. In addition, hydrogen-producing MRs are a potential avenue to alleviate carbon emissions. However, material availability, Pd cost, and scale-up potential on the order of 1.5 million m 3 /day may be limiting factors preventing wider application of Pd-based membranes. Regarding the economic production of hydrogen, the benchmark by the year 2020 has been determined and set in place by the U.S. DOE at less than $2.00 per kg of produced hydrogen. While the established SMR process can easily meet the set limit by DOE, other carbon-free processes such as water electrolysis, electron beam radiolysis, and gliding arc technologies do not presently meet this requirement. In particular, it is expected that the cost of hydrogen produced from natural gas without CCUS will remain the lowest among all of the technologies, while the hydrogen cost produced from an SMR plant with solvent-based carbon capture could be twice as expensive as the conventional SMR without carbon capture. Pd-based MRs have the potential to produce hydrogen at competitive prices with SMR plants equipped with carbon capture. Despite the significant improvements in the electrolysis technologies, the cost of hydrogen produced by electrolysis may remain significantly higher in most geographical locations compared with the hydrogen produced from fossil fuels. The cost of hydrogen via electrolysis may vary up to a factor of ten, d epending on the location and the electricity source. Nevertheless, due to its modular nature, the electrolysis process will likely play a significant role in the hydrogen economy when implemented in suitable geographical locations and powered by renewable electricity. This review provides a critical overview of the opportunities and challenges associated with the use of the MRs to produce high-purity hydrogen with low carbon emissions. Moreover, a technoeconomic review of the potential methods for hydrogen production is provided and the drawbacks and advantages of each method are presented and discussed.